Enhancing remanufacturing: Studying networks and sustainability to support Finnish industry - Iris Karvonen; Kim Jansson; Hannele Tonteri; Saija Vatanen; Mikko Uoti (Journal of Remanufacturing, 2015)
Through the extension of product life, remanufacturing contributes to sustainability, saving energy and materials, and reducing waste and emissions. Today, the application of remanufacturing has far from reached its potential, and it is only common in specific industrial fields and geographic areas. In Finland the awareness of the concept and the potential is low and the implementation is at a low level even if some companies have identified its business benefits. To advance remanufacturing, better understanding is needed about the benefits, challenges and practices as well as how the remanufacturing system could be built. Networking is important to Finnish companies in new product manufacturing and even more in remanufacturing as additional activities and actors are needed. Different forms of networking may be needed in different cases. Thus, based on the results of a Finnish research project, this paper discusses the types of enterprise collaboration in remanufacturing. Additionally, sustainability assessment of remanufacturing is discussed to understand the benefits. Both the topics relate to the main research question of the project: 'How remanufacturing could be applied and promoted in Finnish industry?' The study uses information collected from Finnish industry and cases described in literature. Actors needed in a remanufacturing system are identified and a scheme for a classification for collaboration network types is presented. Assessment of sustainability of remanufacturing is discussed through a case study.
Keywords: 650; Remanufacturing; Life cycle thinking; Remanufacturing networks; Collaboration; Sustainability evaluation